Archeological Echocardiography: Digitization and Speckle Tracking Analysis of Archival Echocardiograms in the HyperGEN Study. Issue 3 (3rd November 2015) - Aguilar, Frank G.; Selvaraj, Senthil; Martinez, Eva E.; Katz, Daniel H.; Beussink, Lauren; Kim, Kwang‐Youn A.; Ping, Jie; Rasmussen‐Torvik, Laura; Goyal, Amita; Sha, Jin; Irvin, Marguerite R.; Arnett, Donna K.; et al.
Abstract : Background: Several large epidemiologic studies and clinical trials have included echocardiography, but images were stored in analog format and these studies predated tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE). We hypothesized that digitization of analog echocardiograms, with subsequent quantification of cardiac mechanics using STE, is feasible, reproducible, accurate, and produces clinically valid results. Methods: In the NHLBI HyperGEN study (N = 2234), archived analog echocardiograms were digitized and subsequently analyzed using STE to obtain tissue velocities/strain. Echocardiograms were assigned quality scores and inter‐/intra‐observer agreement was calculated. Accuracy was evaluated in: (1) a separate second study (N = 50) comparing prospective digital strain versus post hoc analog‐to‐digital strain, and (2) in a third study (N = 95) comparing prospectively obtained TDI e' velocities with post hoc STE e' velocities. Finally, we replicated previously known associations between tissue velocities/strain, conventional echocardiographic measurements, and clinical data. Results: Of the 2234 HyperGEN echocardiograms, 2150 (96.2%) underwent successful digitization and STE analysis. Inter/intra‐observer agreement was high for all STE parameters, especially longitudinal strain (LS). In accuracy studies, LS performed best when comparing post hoc STE to prospective digital STE for strain analysis. STE‐derived e' velocities correlated with, but systematically underestimated, TDI e' velocity. Several known associations between clinical variables and cardiac mechanics were replicated in HyperGEN. We also found a novel independent inverse association between fasting glucose and LS (adjusted β = −2.4 [95% CI −3.6, −1.2]% per 1‐SD increase in fasting glucose; P < 0.001). Conclusions: Archeological echocardiography, the digitization and speckle tracking analysis of archival echocardiograms, is feasible and generates indices of cardiac mechanics similar to contemporary studies.